Hubungan asupan protein dan kadar kreatinin penderita gagal ginjal kronik dengan hemodialisis - Amilia Yuni Damayanti (Darussalam Nutrition Journal, 2017)
Chronic Renal Failure (CRF) is a disease characterized increase in progressive renal failure which is irreversible. CRF as known as a disease associated with food intake expecially plant protein and heme protein that causes morbidity and mortality CRF patients. This research aims to know the associations between intake of plant protein and heme protein with creatinin level in CRF on hemodialysis. Type of the research is analytical observasional research with cross-sectional approach. Techniques subjects using consecutive sampling with total research subjects 22 subjects. Percentage plant protein and heme protein using recall 3x24 hour method, creatinin level obtained from spectrofotometric method. The data analysis using pearson product moment. An adequate of plant protein intake in CRF on hemodialysis outpatients only 4,5 % and 27,3 % of heme protein. But the intake of plant protein that was not adequate as big as 95,5 % and 72,7 of heme protein. Most of patients have high creatinin level (86,4 %).  There was no associations between intake of plant protein and heme protein creatinin level.